150 Incremental value of cardiopulmonary exercise testing in intermediate-risk pulmonary arterial hypertension. (8th December 2021) - Badagliacca, Roberto; Rischard, Franz; Giudice, Francesco Lo; Howard, Luke; Papa, Silvia; Valli, Gabriele; Manzi, Giovanna; Sciomer, Susanna; Palange, Paolo; Garcia, Joe G. N; Vanderpool, Rebecca; Rinaldo, Rocco; et al.
Abstract: Aims: Risk assessment in pulmonary arterial hypertension (PAH) is essential for prognostication. However, the majority of patients end-up in an intermediate risk status despite targeted-therapy, offering insufficient guidance in clinical practice. The added value of cardiopulmonary exercise testing (CPET) in this setting remains undefined. Methods and results: Two independent cohorts with idiopathic PAH at intermediate risk were used to develop ( n = 124) and externally validate ( n = 143) the prognostic model. Risk assessment was based on the simplified version of the ESC/ERS guidelines score. The same definition of clinical worsening (CW) was used for both cohorts. Discrimination and calibration were assessed. Seventy-four derivation cohort patients experienced CW (51.2%) during a median of 34 months. Stroke volume index (SVI) and 6-min walk-distance (6MWD) were independent predictors of CW. With addition of CPET variables, SVI and VO2 peak independently improved the power of the prognostic model, determined by the integrated discrimination integral (IDI) index. ROC-derived cut-off values for SVI and VO2 peak were 34 and 14 ml/kg/min, respectively. Forty-eight validation cohort patients experienced CW (33.5%) during a median of 27 months follow-up. Different combinations of cut-off values of SVI and VO2 peak defined three meaningful groups showing good discrimination and calibration. The event-free survival rates at 1, 2, and 3 years were, respectively, 96%, 89%, and 89% for high SVI/high VO2 peak combination; 85%, 73%, and 61% for high SVI/low VO2 peak; and 80%, 70%, and 56% for low SVI/low VO2 peak. Conclusions: Combinations of VO2 peak and SVI during follow-up is important in the prognostication of intermediate-risk prevalent patients with idiopathic PAH.